Determinants of Accounting Students' Perception Toward Online Lending and FinTech Applications - Robertus Cio; Agnes Quartina Pudjiastuti; Suhendri, Hendrik (International Research and Development for Human Beings (IRDH), 2025)
This study aims to identify the factors that influence accounting students' perceptions of online loans and financial technology. A quantitative approach was employed, with the sample selected using the Stratified Random Sampling method, resulting in a total of 100 respondents. Data were collected through questionnaires, and the data analysis was carried out using multiple linear regression with the assistance of SPSS version 26. The findings reveal that variables such as age, gender, number of loan applications, academic cohort, social environment, specific knowledge about online loans, financial literacy, and digital literacy have a significant and positive influence on accounting students’ perceptions of online loans at UNITRI Malang. These factors were also found to significantly and positively affect their perceptions of financial technology.